Desempeño ambiental de dos municipios conurbanos de Bogotá en contextos de integración urbano–rural del proyecto Región Capital (2019)
During this first stage of diagnosis, analysis of problem-oriented economyand environment axis is focused on identifying local environmental issues, ofmajor significance in the relationship company - Nature of the municipalitiesin the urban edge; to advance this process, a qualitative exploratory phase,which identifies and describes most important environmental problems ofthe socioeconomic reality of the municipalities around the perception of therural community in relation applies: degraded natural resources, the vulnerablepopulation exposed to environmental impact, social costs of local environmentalpolicy interaction municipalities of Chia and La Calera (Colombia) economicactivities and natural systems, institutions and degree. Thus, contaminationproblems identified in the target towns, establish a challenge with cooperationand articulation of wills between the local and regional economic and socialorganizations to transform the negative effects in the agricultural industry ofthe peripheral towns and the relation with the big urban centers.